The Non-Mevalonate Pathway to Isoprenoid Biosynthesis: A Potential Source of New Drug Targets - Anna K. H. Hirsch; François Diederich (CHIMIA, 2008)
Isoprenoids are an essential class of natural products with a myriad of biological functions. All isoprenoids are assembled using two common five-carbon precursors, isopentenyl diphosphate (IPP) and dimethylallyl diphosphate (DMAPP) that are biosynthesized via two completely independent routes: the mevalonate and the non-mevalonate pathway. While the former is used by humans, the latter is employed exclusively by a number of important pathogens such as the malarial Plasmodium falciparum parasite or the tuberculosis-causing Mycobacterium tuberculosis bacterium. Hence, the constituent enzymes are potentially very interesting drug targets in the ongoing fight against diseases, whose treatment has been complicated by the emergence of multi-drug resistance. After a short description of the biosynthetic pathway, an overview will be given on the known inhibitors of the individual enzymes.